The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/01926230252824725
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Adverse and Nonadverse Effects in Toxicity Studies

Abstract: One of the most important quantitative outputs from toxicity studies is identi cation of the highest exposure level (dose or concentration) that does not cause treatment related effects that could be considered relevant to human health risk assessment. A review of regulatory and other scienti c literature and of current practices has revealed a lack of consistency in de nition and application of frequently used terms such as No Observed Effect Level (NOEL), No Observed Adverse Effect Level (NOAEL), adverse eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 6 publications
1
153
0
6
Order By: Relevance
“…To help address this issue, a European Centre for Ecotoxicology and Toxicology of Chemicals (ECETOC) initiative, reporting in 2002, organized a task force for addressing adversity in toxicology studies. This effort resulted in a publication by Lewis et al in (2002) that provided the following definitions, which were more specific to findings in toxicologic pathology:…”
Section: Past Definitions Of Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“…To help address this issue, a European Centre for Ecotoxicology and Toxicology of Chemicals (ECETOC) initiative, reporting in 2002, organized a task force for addressing adversity in toxicology studies. This effort resulted in a publication by Lewis et al in (2002) that provided the following definitions, which were more specific to findings in toxicologic pathology:…”
Section: Past Definitions Of Adversitymentioning
confidence: 99%
“…Conversely, extremely rare or unfamiliar findings may increase uncertainty regarding adversity and result in a higher degree of conservatism. Factors indicating that an intergroup difference is probably not a test item-related effect include lack of a clear dose-response or pairwise differences between groups, high variability or imprecision of the end point, incidence values within the normal range of biological variation, and/or lack of biological plausibility taking into account preexisting knowledge of the test item (adapted from Lewis et al 2002).…”
Section: Exacerbation Of Spontaneous/background Findingsmentioning
confidence: 99%
“…. affects the performance of the whole organism's ability to respond to an additional environmental challenge'' (Lewis et al 2002). Another widely accepted definition is that an adverse effect is ''a change in morphology, physiology, growth, reproduction, development, or life span of an organism which results in impairment of functional capacity or impairment of capacity to compensate for additional stress or increased susceptibility to the harmful effects of other environmental influences'' (WHO/IPCS [International Programme on Chemical Safety] 2004).…”
Section: Hepatic Hypertrophy: Adverse Versus Non-adversementioning
confidence: 99%
“…The standard benchmarks typically used in toxicology studies-including the no-observed-effect level (NOEL), no-observed-adverse-effect level (NOAEL), and lowestobserved-adverse-effect level (LOAEL)-are usually not applicable with cytotoxic oncology molecules (Dorato and Englehardt 2005;Lewis et al 2002). Rather, benchmarking in rat and dog studies with oncology therapeutics includes the dose that results in 10% mortality over the duration of the study (STD 10 ) in rats, and the highest non-severely toxic dose (HNSTD), which is defined as a dose that does not produce death or moribundity during a study in rats or dogs.…”
Section: Definitions Of Benchmark Doses In Oncology Testingmentioning
confidence: 99%